Gambaran Kepuasan Masyarakat Terhadap Pelayanan Kesehatan Posyandu Melati Asri 1 Kelurahan Wonosari Kecamatan Ngaliyan Kota Semarang - Yuniarti, Christina Ary (Universitas Ivet, 2025)
The Integrated Health Service Post (Posyandu) is a form of Community-Based Health Effort (UKBM) that is managed by, from, for, and with the community. Its primary aim is to empower the community and facilitate access to basic health services. This study aims to identify the completeness of available health services and to assess the level of community satisfaction with the services provided at Posyandu Melati Asri. The research employed a qualitative descriptive approach, with data collection methods including observation, interviews, and questionnaires filled out by 14 respondents. Data analysis was conducted using the interactive model approach. The survey results indicate that Posyandu Melati Asri is divided into two units Melati Asri 1 and Melati Asri 2 due to the extensive coverage area of the kelurahan. The services offered include child weighing, health counseling, nutritional status monitoring, vector control activities, diarrhea prevention, and immunizations. Community satisfaction data show that 43% of respondents rated the services as “good,” while 57% rated them as “fair.” In conclusion, the majority of the respondents considered the healthcare services at Posyandu Melati Asri 1 to be in the “fair” category.